Journey to Smart Bangladesh: Realities and Challenges - Ahmed, Tanji; Hasan, Nazmul; Akter, Runa (CV. Literasi Indonesia, 2023)
Bangladesh, a nation renowned for its resilience and quick growth, has started on a transformational path to become a